Significant learning experiences for english foreign language students (2010)
This action research examines experiences that students in a grade 10 EFL class had with redesigning a grammar-unit into a topic-based unit. Strategies were formulating significant learning goals and objectives, and implementing and reflecting on activities with three dimensions of Dee Fink’s (2003) taxonomy of significant learning: the human dimension, integration, and application. Students reported positive perceptions about learning with and about others, learning about themselves, integrating language and topics to their lives, and recycling and applying topics to other formats. They became more active and reflective language learners. Difficulties were linking significant unit goals and objectives to all participants’ needs and interests, students’ initial unwillingness to learn about others, and students’ limited proficiency for integrating and applying English. Esta investigación acción examina las experiencias que estudiantes de un grado 10.o de inglés como lengua extranjera tuvieron durante el rediseño de una unidad gramatical a una unidad temática. Las estrategias fueron la formulación de metas y objetivos de aprendizaje significativo, y la implementación y la reflexión sobre actividades con tres dimensiones de la taxonomía de aprendizaje significativo de Dee Fink (2003): la dimensión humana, la integración y la aplicación. Los estudiantes reportaron percepciones positivas al aprender con otros, acerca de otros y acerca de ellos mismos. También integraron el lenguaje y los temas a sus vidas, reciclaron y aplicaron los temas en otros formatos. Los estudiantes se convirtieron en aprendices más activos y reflexivos. Las dificultades fueron: la vinculación de las metas y los objetivos significativos de la unidad con las necesidades y los intereses de los participantes; la falta de disponibilidad inicial de los estudiantes para aprender acerca de otros, y su bajo dominio para integrar y aplicar el inglés.